Aporte de las remesas al crecimiento económico de Colombia: departamentos de Risaralda, Quindío, Caldas y Valle del Cauca 2009–2017 (2019)
From the end of the 20th century and the beginning of the 21st century, the constant migration of Colombian citizens abroad began, mainly in more developed countries with better welfare conditions, due to the difficult economic and social conditions that occur in the country. This also led to increased income in remittances by migrants to their respective families in order to support their livelihoods in the difficult situation in which they find themselves. The large departments that receive remittances from 2009 to 2017 have been Valle del Cauca being always the leader, and the three that make up the Eje Cafetero, that is, Caldas, Quindío and Risaralda. These four departments receive about 45% of the total remittances entered into the country. Therefore, this income has made for such departments the quality of life is viable by helping to have an economic growth in these, since it helps domestic consumption of goods and services, along with trade in these, gives stability to families when these suffer from unemployment problems, and positive support is also generated in the construction activity through investments in it by the host families. The Banco de la República is the entity in charge of controlling the entry of remittances into the country.